2021
DOI: 10.3390/jcm10143144
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Azoospermia in Men with Infertility

Abstract: The differential diagnosis between obstructive and nonobstructive azoospermia is the first step in the clinical management of azoospermic patients with infertility. It includes a detailed medical history and physical examination, semen analysis, hormonal assessment, genetic tests, and imaging studies. A testicular biopsy is reserved for the cases of doubt, mainly in patients whose history, physical examination, and endocrine analysis are inconclusive. The latter should be combined with sperm extraction for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 97 publications
1
49
0
1
Order By: Relevance
“…It inevitably leads to infertility [ 1 ]. Worldwide, it is estimated that 1% of men of reproductive age and up to 10% of men with infertility are azoospermic [ 2 ]. Azoospermia is classified as obstructive and non-obstructive [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It inevitably leads to infertility [ 1 ]. Worldwide, it is estimated that 1% of men of reproductive age and up to 10% of men with infertility are azoospermic [ 2 ]. Azoospermia is classified as obstructive and non-obstructive [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This problem affects about 10–15% of married couples, and the male factor is responsible for half of the cases [ 1 ]. Several causes are incriminated such as hormonal abnormalities, infections, genetic disorders, testicular cancer, varicocele, and others [ 2 ]. Testicular tuberculosis is a rare cause of male infertility in underdeveloped countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing the obstruction of the vas deferens by microsurgery is the first choice for treatment of OA, while intracytoplasmic sperm injection (ICSI) and testicular sperm extraction (TESE) are more recommended for NOA [ 6 ]. Hence, the differential diagnosis of OA and NOA is of great significance because it is directly related to the choice of treatment methods [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sperm retrieval is successful in no more than 58% of men with NOA, provided that the most effective surgical technique, namely, microdissection testicular sperm extraction (mTESE), is used [ 3 ]. In the first article of the present Special Issue, Danilo L. Andrade, Marina C. Viana and Sandro C. Esteves showed that the differential diagnosis between OA and NOA may be effectively accomplished in most patients by means of a standardized male infertility workup, which should include a detailed medical history, a careful physical examination with a focus on secondary sexual characteristics, a semen analysis obtained on at least two occasions and assessed according to the World Health Organization, hormonal evaluation (serum FSH, LH, prolactin and testosterone levels), genetic tests (karyotype and Y chromosome microdeletion analysis, screening for cystic fibrosis transmembrane conductance regulator gene mutations), and a scrotal and transrectal ultrasound, with testis biopsy being reserved only for the cases of doubt [ 4 ].…”
mentioning
confidence: 99%